Modelling intelligent multi-modal transit systems - Nuzzolo, Agostino; Lam, William H. K. (CRC Press/Taylor & Francis, 2017)
The book will be of interest to urban planners, public transport agency technicians, Decision Support System (DSS) tool developers, students and researchers.